hiPSC-Based Model of Prenatal Exposure to Cannabinoids: Effect on Neuronal Differentiation - Miranda, Cláudia C.; Barata, Tiago; Vaz, Sandra H.; Ferreira, Carla; Quintas, Alexandre; Bekman, Evguenia P. (Frontiers in Molecular Neuroscience, 2020)
Phytocannabinoids are psychotropic substances of cannabis with ability to bind endocannabinoid receptors that regulate synaptic activity in the central nervous system (CNS). Synthetic cannabinoids (SC) emerged as popular alternative to cannabis. Most of these substances are synthetic analogues of Δ9-tetrahydrocannabinol (Δ9-THC)¬, the psychotropic compound of cannabis, acting as agonists of endocannabinoid receptor CB1. SC are easily available, and their molecular structure is always changing, increasing the hazard for general population. The popularity of cannabis and its derivatives may lead, and often does, to child’s exposure to cannabis both in utero and through breastfeeding by a drug-consuming mother. Prenatal exposure to cannabis has been associated with altered rate of mental development and significant changes in nervous system functioning. However, the understanding of mechanisms of its action on developing human CNS is still lacking. We investigated the effect of continuous exposure to cannabinoids on developing human neurons, mimicking the prenatal exposure by drug-consuming mother. Two human induced pluripotent stem cells (hiPSC) lines were induced to differentiate into neuronal cells and exposed for 37 days to cannabidiol (CBD), Δ9-THC, and two SCs, THJ-018 and EG-018. Both Δ9-THC and SC, at 10 µM, promote precocious neuronal and glial differentiation, while CBD at the same concentration is neurotoxic. Neurons exposed to Δ9-THC and SC show abnormal functioning of voltage-gated calcium channels when stimulated by extracellular potassium. In sum, all studied substances have profound impact on the developing neurons, highlighting the importance of thorough research of the impact of prenatal exposure to natural and synthetic cannabinoids.